Kedudukan Ijtihad, Taqlid, dan Fatwa Dalam Kajian Hukum Islam - St. Halima Sari; Muhammad Maqbul; Nadief Rizqullah Tahir; Besse Ruhaya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Ijtihad, taqlid, and fatwa are fundamental concepts in Islamic law that serve as essential mechanisms for addressing legal issues arising from the continuous development of society. This paper aims to explain the definitions of ijtihad, taqlid, and fatwa; the requirements and pillars of ijtihad and fatwa; their classifications; the methods of ijtihad in Islamic law; the legal status of ijtihad and taqlid; and the products of ijtihad and fatwa in contemporary society. This study employs a library research method by examining various scholarly sources related to Islamic law. The discussion reveals that ijtihad is the earnest intellectual effort of a qualified mujtahid to derive Islamic legal rulings from the Qur'an, the Sunnah, and other recognized legal sources. Taqlid refers to following the opinions of qualified Islamic scholars by those who lack the ability to perform ijtihad, while a fatwa is a legal opinion issued by a mufti in response to specific questions and is not legally binding in the same way as a court judgment. In the modern era, ijtihad and fatwa play a strategic role in addressing contemporary issues such as Islamic finance, digital transactions, healthcare, and technological advancements, ensuring that Islamic law remains relevant, dynamic, and capable of promoting the public interest (maslahah).